The Influence of Financial Factors and Audit Quality on Earnings Management with Institutional Ownership as Moderating - Wijayanti, Reka (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2022)
The purpose of this study is to empirically determine the effect of earning power, leverage, firm size, financial distress, and audit quality on earnings management and whether institutional ownership can affect the relationship between earning power and leverage on earnings management in listed basic industrial and chemical manufacturing companies on the IDX. The type of research used in this research is quantitative research. The approach used in this research is the causality approach. The population and sample in this study were manufacturing companies in the basic industry and chemical sectors listed on the Indonesia Stock Exchange in 2016-2019 with a total of 52 companies. The data analysis method used Moderated Regression Analysis (MRA). The results of this study show that: earning power has no effect on earnings management, leverage has a negative effect on earnings management, firm size has a positive effect on earnings management, financial distress has a negative effect on earnings management, audit quality has a negative effect on earnings management, institutional ownership does not strengthen the negative effect of earning power on earnings management, and institutional ownership does not weaken the positive influence between leverage and earnings management.